Viral Sequencing to Investigate Sources of SARS-CoV-2 Infection in US Healthcare Personnel. (15th April 2021) - Braun, Katarina M; Moreno, Gage K; Buys, Ashley; Somsen, Elizabeth D; Bobholz, Max; Accola, Molly A; Anderson, Laura; Rehrauer, William M; Baker, David A; Safdar, Nasia; Lepak, Alexander J; O'Connor, David H; et al.
Abstract: Background: Healthcare personnel (HCP) are at increased risk of infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We posit that current infection control guidelines generally protect HCP from SARS-CoV-2 infection in a healthcare setting. Methods: In this retrospective case series, we used viral genomics to investigate the likely source of SARS-CoV-2 infection in HCP at a major academic medical institution in the Upper Midwest of the United States between 25 March and 27 December 2020. We obtained limited epidemiological data through informal interviews and review of the electronic health record and combined this information with healthcare-associated viral sequences and viral sequences collected in the broader community to infer the most likely source of infection in HCP. Results: We investigated SARS-CoV-2 infection clusters involving 95 HCP and 137 possible patient contact sequences. The majority of HCP infections could not be linked to a patient or coworker (55 of 95 [57.9%]) and were genetically similar to viruses circulating concurrently in the community. We found that 10.5% of HCP infections (10 of 95) could be traced to a coworker. Strikingly, only 4.2% (4 of 95) could be traced to a patient source. Conclusions: Infections among HCP add further strain to the healthcare system and put patients, HCP, and communities at risk. We found no evidence for healthcare-associated transmission in the majority of HCP infections evaluated. Although we cannot rule out the possibility of cryptic healthcare-associated transmission, it appears that HCP most commonly become infected with SARS-CoV-2 via community exposure. This emphasizes the ongoing importance of mask wearing, physical distancing, robust testing programs, and rapid distribution of vaccines. Abstract : The majority of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections in 95 healthcare personnel (HCP) could not be linked to a patient or coworker. Infection control procedures, consistently followed, offer significant protection to HCP caring for patients with SARS-CoV-2.